Carrion, context, and lure development: the relative importance of sensory modalities to foraging brown treesnakes (Boiga irregularis) - Shivik, John A., author; Clark, Larry, advisor; Wright, William G., advisor; Packard, Gary C., committee member; Andelt, William F., committee member; Rodda, Gordon H., committee member (Colorado State University. Libraries, 1999)
Since the brown treesnake was introduced on Guam, it has caused the decline and extinction of avifauna and herpetofauna, numerous power outages, loss of domestic animals, and is a threat to other land masses. Trapping, using live mice as lures, is an effective method for removing brown treesnakes from an area, but using live mice in traps presents animal care and maintenance problems. These problems can be alleviated if an effective artificial line for brown treesnakes can be developed, but effective lure development necessitates further study of the sensory biology and foraging ecology of brown treesnakes. By performing experiments in the laboratory at Ft. Collins and in field conditions on Guam, I have determined that both visual and odor cues are important for attracting brown treesnakes when live mice are used as lures. When using mouse carrion, however, the importance of visual cues is reduced. I identified and tested major components of dead mouse odor, as well as a variety of natural compounds for attracting brown treesnakes, but did not find a single chemical that would lure snakes into traps. The attractiveness of dead mouse odor varies widely between seasons, and future lures for brown treesnakes should incorporate the concept of a "super normal stimulus suite" using multiple sensory cues from an odorized mechanical model. In light of these results, I discuss evolutionary trends in scavenging among taxa.
Keywords: zoology; forestry